Land tenure and conflict propagation: critical geopolitics from the rural grassroots in North Kivu (Democratic Republic of Congo) - Pottek, Elias; Kasisi, Robert; Herrmann, Thora (Cahiers de géographie du Québec, 2016)
In its most recent history, the Democratic Republic of Congo (DRC) has taken central stage in two interstate wars and multiple civil conflicts with trans-border dynamics. Somewhat less well known is the fact that the DRC is also a prime example of a different, continent-wide African problematic: the precarity of land rights and resulting conflicts over land tenure. This paper is part of a study that explores interactions between tenure conflicts at the micro-level and the larger ethnic, civil and interstate conflicts of the region. In its first part, the article discusses conflict study approaches from various disciplines and the published literature and makes the case for a multi-scalar critical geopolitical conflict analysis. The second part presents case studies, the survey questionnaire and interview based fieldwork results that reveal the near ubiquity of tenure conflicts in North Kivu and show the causes of these conflicts and how they tend to proliferate at the rural grassroots base and subsequently extend upwards.